2023
DOI: 10.1097/md.0000000000032761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of overground powered exoskeleton for gait training in patients with subacute stroke: A randomized controlled pilot trial

Abstract: Background: To investigate the efficacy and usefulness of 12 sessions of overground robot-assisted gait training (RAGT) in subacute stroke patients. Methods: In this pilot study, 17 subacute stroke survivors were randomly assigned to the intervention (n = 9) and control (n = 8) groups. In addition to the conventional stroke neurorehabilitation program, the intervention group received 30 minutes of overground exoskeletal RAGT, while the control group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(62 reference statements)
0
6
0
1
Order By: Relevance
“…Also, Yoo et al (2023) found a signi cant improvement in the BBS outcome in groups, but there was no signi cant difference between the groups. Also, the TUG outcome was signi cantly improved only in the robotic group (9). In the study of Miyagawa et al (2023), despite improvement in both groups, no signi cant differences were observed between the two groups in 6MWT, TUG, and BBS outcomes (25).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Also, Yoo et al (2023) found a signi cant improvement in the BBS outcome in groups, but there was no signi cant difference between the groups. Also, the TUG outcome was signi cantly improved only in the robotic group (9). In the study of Miyagawa et al (2023), despite improvement in both groups, no signi cant differences were observed between the two groups in 6MWT, TUG, and BBS outcomes (25).…”
Section: Discussionmentioning
confidence: 80%
“…Compared to xed-type robots, the use of overground robots like Hip Exoskeleton Assistive (HEXA) is more economical and provides more natural sensory inputs in walking by allowing the patient to explore the environment. However, due to the newness of this approach, few studies have been done in this eld (9). However, in some of these studies, the interaction of patients with the robot, regarding the ability to adjust the force, was limited due to either cognitive disorders such as cerebral palsy (10) or complete loss of movement in spinal cord injury patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…Tahap awal diharapkan tidak terjadi komplikasi sekunder dan menjaga fungsi yang tersisa. Menurut (Yoo et al, 2023) tahap ini dimulai sesegera mungkin saat kondisi secara umum membolehkan. Fase lanjutan diharapkan memperoleh independen fungsional dalam gerak serta ADL.…”
Section: Pembahasanunclassified
“…Throughout the rehabilitation landscape, we need to find effective modalities to deliver individualized high-intensity rehabilitation for gait training. Lower extremity exoskeletons are currently being utilized for stroke gait rehabilitation and recent research has demonstrated improvements in functional recovery [5,6,7,8]. Robotic exoskeletons (REs) are electromechanical devices that provide assistance as needed by the user to ambulate while providing stability and balance.…”
Section: Introductionmentioning
confidence: 99%
“…REs provide the user with consistent, and goal-directed repetition of movement [9,10]. In addition, REs also have the potential to provide increased number of steps in a session (dosing) as well as intensity (heart rate) in a consistent and controlled training environment, which is ideal to induce neuroplasticity [6,11]. Previous research in stroke motor rehabilitation has demonstrated that increasing the dosing and intensity is a critical variable of rehabilitation interventions that can facilitate plasticity of neuromuscular system and result in improved locomotor function [12].…”
Section: Introductionmentioning
confidence: 99%